George Hunsinger as Theological Interpreter of the Scriptures - O’Collins, Gerald (Asian Horizons, 2024)
After years of studying and expounding Karl Barth, George Hunsinger founded the National Religious Campaign against Torture (NRCAT). Inspired by Thomas Torrance, he moved on to exploring Eucharistic theology; Torrance paid much more attention than Barth to Christ’s priestly office. Hunsinger has turned to interpreting theologically the Scriptures, and published books on Matthew’s version of the Beatitudes and Paul’s Letter to the Philippians.